APLIKASI PENGOLAHAN DATA PENJUALAN (STUDI KASUS : TOKO NET CELLINDO JAMBI): Application, PHPMyAdmin, Processing Data, Store, Visual Basic .NET 2010. - -, Lisdarti (LP2M Universitas Nurdin Hamzah, 2019)
Information Systems (SI) are a combination of information technology and activities of people who use technology that supports operations and management. The application is a useful component as a medium for managing data or various other activities such as making or processing documents and files. Net Cellindo is a spare parts shop and mobile service for all brands in Jambi City, Net Cellindo was started to be established in Jambi City on September 17, 2016 and initiated by Hamsun the owner of Net Cellindo. Initially Cellindo Net only existed in Jambi City, but along with the highly developed technological developments in the business world, Net Cellindo has now opened 4 branches in major cities, namely, Jambi, Palembang, Lampung and Jakarta. Processing data is the manipulation of data into a form that is more useful and more meaningful, contains information. The results of the study concluded that with the application of sales data processing in the Net Cellindo Store, it can help collection of sales items and sales reports that are more detailed to be understood.